1985
DOI: 10.2307/3583525
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic Cell Transformation by Heavy Charged Particles

Abstract: With confluent cultures of the C3H10T1/2 mammalian cell line, we have investigated the effects of heavy-ion radiation on neoplastic cell transformation. Our quantitative data obtained with high-energy carbon, neon, silicon, argon, iron, and uranium particles show that RBE is both dose- and LET-dependent for malignant cell transformation. RBE is higher at lower doses. There is an increase of RBE with LET, up to about 100-200 keV/micron, and a decrease of RBE with beams of higher LET values. Transformation lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…Nevertheless, the difference between the abilities of carbon ion and iron ion radiation to induce anchorage-independent growth of the surviving population of the irradiated cells suggests a possible difference in the mechanism(s) by which the different HZE particles affect the carcinogenic process in the irradiated cells. Other investigators noted major differences in the RBE values for transformation induced by radiation from different heavy ions, with the RBEs varying in a LET-dependent manner up to 80-120 keV/µm (10) or 100-200 keV/µm (11). The LET of the carbon ions (13.6 kev/µm) was less than one tenth of that of the iron ions (150 kev/µm) used in this study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Nevertheless, the difference between the abilities of carbon ion and iron ion radiation to induce anchorage-independent growth of the surviving population of the irradiated cells suggests a possible difference in the mechanism(s) by which the different HZE particles affect the carcinogenic process in the irradiated cells. Other investigators noted major differences in the RBE values for transformation induced by radiation from different heavy ions, with the RBEs varying in a LET-dependent manner up to 80-120 keV/µm (10) or 100-200 keV/µm (11). The LET of the carbon ions (13.6 kev/µm) was less than one tenth of that of the iron ions (150 kev/µm) used in this study.…”
Section: Discussionmentioning
confidence: 50%
“…In general, it is expected that for various types of ionizing radiations, including heavy ions, the RBE is likely to increase with LET for cytotoxic, mutagenic and carcinogenic effects, reaching a maximum at approximately 100 keV/µm (11,13). The findings presented for the cytotoxicity results, in which the effects of carbon ions, with a LET of 13.6 KeV/µm, are comparable to those of iron ions, with a LET of 150 KeV/µm, are noteworthy surprising given the expected relationship between RBE and LET.…”
Section: Discussionmentioning
confidence: 99%
“…Predictions will be made for cell death (loss of reproductive capability) and neoplastic transformations of C3H10Tlj2 cells. The response parameters of Table 1 were found from the delayed plating experiments of Yang et al (1985) and Waligorski et al (1987). In Fig.…”
Section: Rbe = D(_a_)i/md(i/m-i)mentioning
confidence: 99%
“…Many researchers have reported that the LETrelative biological effectiveness (RBE) curves for different biological endpoints, such as cell killing, mutation induction and in vitro cell transformation are different (Skarsgard et al, 1967;Yang et al, 1985;Tsuboi et al, 1992;Chen et al, 1994;Suzuki et al, 2000;Kiefer et al, 2001;Hamada et al, 2006). It is also known that the peak positions of the LET-RBE curves appear at the LET ranging from 100 to 200 keV/µm, and is shifted to higher LET regions with heavier atomic number ion species even if the LET values are similar (Kraft et al, 1987;Belli et al, 1989;Folkard et al, 1996;Suzuki et al, 1997).…”
Section: Introductionmentioning
confidence: 99%